Juridical analysis of the division of joint property with inherited property after divorce - Siahaan, Rikkot Immanuel; Sidauruk, Jinner (Journal of Law Science, 2025)
The legal consequences arising from divorce cases, one of which is the division of joint property. Which where joint property has been regulated in article 128 kuhperdata regarding the division of joint property after divorce or death. If there are problems in the division of joint property and or inheritance, the husband or wife can file a court lawsuit. In the lawsuit, the important main objective is the existence of mediation outside and inside the court and the judge's consideration in determining the division of property. The aim is to understand the efforts of the parties to be understood before the court decision and the panel of judges in determining the division of joint property due to divorce. This case study is descriptive analytical in nature, namely by analyzing, namely by conducting research using laws and regulations and literature related to the division of joint property after divorce.